Fenologia e caracteres morfofuncionais de espécies de Miconia Ruiz & Pav. (Melastomataceae) em Floresta ciliar, Chapada Diamantina, Bahia - Lima, Mara Rúbia de Oliveira (2013)
Was conducted a study of reproductive phenology of three species of Miconia Ruiz & Pav. (Melastomataceae) occurring in the gallery forest Lençóis river, in Lençóis Municipality (12 º 27'30 "S and 41 º 27'56" W), Chapada Diamantina, discussing reproductive strategies found in sympatric species with similar morphology of flowers and fruits. The phenological observations were made monthly for 48 months in individuals of the species Miconia alborufescens Naud.,Miconia holosericea (L.) DC. and Miconia prasina (Sw) DC., being accompanied phenophases bud, flower, immature fruit and ripe fruits. The species exhibited a pattern reproductive annual, seasonal, sequential, varying its duration. The offer of flowers occurred typically the beginning of the rainy season and no overlap between species. The offer of fruits occurred since the mid rainy season and the dry season without overlapping. The circular statistical tests indicated strong seasonality of fenofases. The irregularity of rainfall and prolonged drought occurred in the last year of observation influence at the time of the manifestation of reproductive phenology M. holosericea and M. prasina, but they fit for the supply of the resource was not superimposed, favoring the maintenance of pollinators and dispersers to these associates.